Chromatographic single-step purification of tagless proteins using gp41-1 split inteins - Knapp, Michael; Kohl, Vanessa; Best, Tatjana; Rammo, Oliver; Ebert, Sybille (Frontiers in Bioengineering and Biotechnology, 2024)
The current trend in biopharmaceutical drug manufacturing is towards increasing potency and complexity of products such as peptide scaffolds, oligonucleotides and many more. Therefore, a universal affinity purification step is important in order to meet the requirements for cost and time efficient drug production. By using a self-splicing intein affinity tag, a purification template is generated that allows for a universal chromatographic affinity capture step to generate a tagless target protein without the use of proteases for further tag removal. This study describes the successful implementation of gp41-1-based split inteins in a chromatographic purification process for e.g. E. coli-derived targets. The tagless target is generated in a single-step purification run. The on-column cleavage is induced by triggering a simple pH change in the buffer conditions without the need for additives such as Zn2+ or thiols. This system has proven to be reusable for at least ten purification cycles that use 150 mM H3PO4 as the cleaning agent.